2015
DOI: 10.5603/cj.a2015.0010
|View full text |Cite
|
Sign up to set email alerts
|

Can thromboembolic risk be associated with erectile dysfunction in atrial fibrillation patients?

Abstract: Background: Erectile dysfunction (ED) is highly prevalent in patients with diseases of cardiovascular system, including patients with atrial fibrillation (AF (Cardiol J 2015; 22, 4: 446-452)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…A recent study by Szymanski et al. showed that in fact, AF patients with ED tend to have higher thromboembolic risk as assessed by the CHA 2 DS 2 ‐VASc score, which follows the above‐mentioned hypothesis and might potentially add to the risk assessment scheme …”
Section: Discussionmentioning
confidence: 74%
“…A recent study by Szymanski et al. showed that in fact, AF patients with ED tend to have higher thromboembolic risk as assessed by the CHA 2 DS 2 ‐VASc score, which follows the above‐mentioned hypothesis and might potentially add to the risk assessment scheme …”
Section: Discussionmentioning
confidence: 74%
“…Patient populations in two articles by Platek et al 10 and Szyma nski et al 17 were similar, and we included the study by Platek et al 10 as it provided more details and updated data for this meta-analysis. After the exclusion of 3338 articles, as they were duplicated, case reports, correspondences, review articles, in vitro studies, animal studies or interventional studies, 36 articles remained for full-length review.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies show that erectile dysfunctions (a non-classical CV risk factor) are highly prevalent in AF patients, and are associated with a greater thromboembolic risk profile [27,28]. Unfortunately, no data are available on the most appropriate mode of treating erectile dysfunction in AF patients.…”
Section: Dihydropyridine Calcium Antagonists Nonementioning
confidence: 99%